DIGITAL TRANSFORMATION IN CONSTRUCTION: A SWOT AND PESTLE ANALYSIS OF INDUSTRY REVOLUTION 4.0 IN MALAYSIA - Lee, Yee Ling; Lim, Siong Kang; Tan, Ooi Kuan; Chong, Siaw Yah; Lim, Ming Han (Journal of Civil Engineering, Science and Technology, 2025)
The construction industry plays a pivotal role in shaping economic growth, environmental sustainability, and societal well-being. It traditionally revolves around three critical dimensions: quality, timeliness, and cost. In the wake of the Fourth Industrial Revolution (IR4.0), the sector is undergoing rapid transformation driven by digital technologies such as robotics, artificial intelligence, and automation. However, the industry's readiness to adopt these innovations remains uneven. This study investigates the current state and future potential of IR4.0 adoption in the construction industry through a structured Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, complemented by a PESTLE framework to assess the external Opportunities and Threats. The findings are based on a scoping review of 144 peer-reviewed publications from the past five years, ensuring up-to-date insights. Results reveal that IR4.0 technologies have contributed to measurable productivity and efficiency gains globally, with countries such as Germany and China leading implementation efforts. The study emphasises that the effective integration of IR4.0 in the Malaysian construction sector requires coordinated efforts across government, academia, and industry to address systemic challenges and skill gaps. Ultimately, the paper highlights both the transformative potential and the strategic imperatives required to future-proof Malaysia's construction ecosystem in the digital age.